Heat-sensitive mutant strain of Neurospora crassa, 4M(t), conditionally defective in 25S ribosomal ribonucleic acid production. - Loo, M W (1981)
A heat-sensitive mutant strain of Neurospora crassa, 4M(t), was studied in an attempt to define its molecular lesion. The mutant strain is inhibited in conidial germination and mycelial extension at the nonpermissive temperature (37 degrees C). Macromolecular synthesis studies showed that both ribonucleic acid (RNA) and protein syntheses are inhibited when 4-h cultures are shifted from 20 to 37 degrees C. Density gradient analysis of ribosomal subunits made at 37 degrees C indicated that strain 4M(t) is deficient in the accumulation of 60S ribosomal subunits in that the ratio of 60S/37S subunits was 0.29:1 compared with 1.6:1 for the parental strain. This phenotype was shown to be the result of a slow rate of processing of, and a deficiency in the amount of, the immediate precursor to 25S ribosomal RNA (the large RNA of the 60S subunit) in the sequence of events constituting the production of mature ribosomal RNAs from the primary transcript of the ribosomal deoxyribonucleic acid, the precursor ribosomal RNA molecule. Analysis of polysomes suggested that the heat-sensitive gene product might function in both the assembly and the function of the 60S ribosomal subunit, since there was a smaller proportion of newly made 60S subunits synthesized at 37 degrees C in the polysome region of the gradients than in the monosome-plus-subunit region. The ribosomal RNA processing defect is apparently responsible for the observed defects in germination and macromolecular synthesis at 37 degrees C, but the precise molecular lesion is not known. On the basis of these results, the heat-sensitive mutant allele in the 4M(t) strain is considered to define the rip1 (ribosome production) gene locus.